Botulism: An Overlooked Cause of Bulbar Weakness in Intensive Care – A Case Report - Louise Adams; Simon Lamquet; Julie Linussio; Tom Van Nieuwenhuysen; Alexandra Vodolazkaia; Marina Mukovnikova; Heleen Parmentier; Sarah Herdewyn (Case Reports in Neurology)
Introduction: Botulism is a rare but potentially life-threatening syndrome caused by botulinum neurotoxin. The classic presentation of botulism is the acute onset of bilateral cranial neuropathies associated with symmetric descending weakness. The antitoxin is the main therapeutic option for botulism, in addition to supportive care with intubation and mechanical ventilation when necessary. The outcome is usually favorable, with a slow but full neurological recovery. This case presents a difficult diagnosis of the sporadic form of adult intestinal toxemia, with a delayed diagnosis. Case Presentation: We report a 64-year-old patient who presented in a confused state with weakness in the limbs, bilateral ptosis, and dysarthria. Because of disease progression with respiratory compromise, the patient was transferred to the intensive care unit (ICU) and intubated. The diagnosis of botulism was eventually confirmed in the stool 46 days after presentation. By the end of follow-up, the patient still received rehabilitation. The outcome was good, except for the concomitant neurodegenerative disorder with the need for institutionalization at a residential care center. Conclusion: This case report illustrates the difficulties in diagnosing a patient with botulism in the ICU, especially if associated with comorbidities. Delayed diagnosis and misdiagnosis are common because of the rarity of the disease and overlapping signs and symptoms with other neurological diseases. Increasing the awareness of this disease is important to prevent mortality and morbidity.